Using land inequality to inform restoration strategies for the Brazilian dry forest - Melo, Felipe P.L.; Mazzochini, Guilherme G.; Guidotti, Vinícius; Manhães, Adriana P. (Landscape and urban planning, 2023)
•Distribution of land and restoration opportunities is highly unequal.•Large landowners retain nearly half of the vegetation deficit.•Numerous smallholders lack restoration incentives.•Restoration planning must account for land inequality. Forest and landscape restoration aims not only to restore ecosystems but to improve people's livelihoods. However, mapping of restoration often neglects key socioeconomic aspects such as land-access inequalities. In this article, we quantify and describe the distribution of vegetation deficits (areas that demand mandatory restoration) across small and large rural properties across 1,204 municipalities of the Brazilian Caatinga biome. We mapped 313,537 ha of vegetation deficit, i.e. areas previously cleared that will need to be restored for legal compliance. This vegetation deficit is almost equally shared between 141,144 smallholders and only 2,986 in large properties. Around half of this vegetation deficit is spatially clumped mainly in the East and along the main river basin of the region dominated by rich large-holders. On the other hand, spatially scattered and poor small landowners hold around another half of the vegetation deficit across several municipalities. Because of such an unequal distribution of native vegetation deficit, we propose three different restoration strategies to account for land-access inequalities and socioeconomic differences at the municipality level. This is one of the first studies to clearly address land inequality and socioeconomic profile of landowners to inform adapted restoration strategies. Restoration planning that ignores land concentration and socioeconomic contexts may reproduce inequalities known to be one of the main causes of ecosystem degradation across Global South countries.